KREASI SABUN DAN LILIN DARI LIMBAH MINYAK JELANTAH SEBAGAI PELUANG BISNIS BAGI WARGA DESA NGASEM - Lulu’ Choir Risalina; Ratna Nabila Permataningrum; Rio Martin; Laily Khasinatil Asror; Alifia Putri Febriyanti (Aplikasia)
There are 2,214 families in Ngasem Village who each produce 1 liter of cooking oil waste every month. From there, there is a need for the treatment of used cooking oil waste in the region so that the waste does not pollute the environment. The processing proposed in this research is the utilization into soap and candles. The implementation of activities uses the CBR (Community-based Research) method. In its stages, there are several series: Determining the target of the workshop, namely the women of PKK and Dasa Wisma of Ngasem Village; observing the condition of the village organization and the type of training that is often promoted; and following up the workshop with materials related to the utilization of used cooking oil waste into creations with business opportunities. Our workshop resulted in a good enthusiasm from the ladies. They were able to grasp the material well and were active in the discussion. Demonstrations were well followed, and participants were able to practice smoothly. This shows an indicator of success in delivering information, especially in terms of calculating prices as the next business opportunity. The price of soap and candle products from used cooking oil can be categorized as affordable with raw materials from daily cooking waste.